2021
DOI: 10.17219/acem/139398
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of vanillin receptors in cancer

Abstract: Natural products play significant roles in the development of novel drugs. One of such compounds is vanillin -a natural substance commonly used in food. Anticancer potential of the substance is continually encouraging researchers to conduct further investigations. A rising number of publications describe the role of 4-hydroxy-3-methoxybenzaldehyde (vanillin) in the process of inhibiting tumor growth. Four vanilloid receptors play significant roles in the response of cancer cells to the natural compound. Each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 98 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…The other compounds of AN also have biological effects, such as vanillin, alphaterpineol, benzyl alcohol, capric acid, resveratrol, quinic acid, chrysophanol, physcion, p-hydroxybenzoic acid, epoxyconiferyl alcohol, protocatechuic acid, isovanillic acid, ferulic acid, vanillic acid and polyphenols. Vanillin has anti-tumor, anti-mutagenic, antioxidant, analgesic and anti-erythrocyte-sickling properties [50]. Alpha-terpineol was demonstrated to have a potential in reducing mechanical hypernociception/inflammatory response, cardiovascular and gastric lesions, anticonvulsant and antidiarrheal activities [51].…”
Section: Othersmentioning
confidence: 99%
“…The other compounds of AN also have biological effects, such as vanillin, alphaterpineol, benzyl alcohol, capric acid, resveratrol, quinic acid, chrysophanol, physcion, p-hydroxybenzoic acid, epoxyconiferyl alcohol, protocatechuic acid, isovanillic acid, ferulic acid, vanillic acid and polyphenols. Vanillin has anti-tumor, anti-mutagenic, antioxidant, analgesic and anti-erythrocyte-sickling properties [50]. Alpha-terpineol was demonstrated to have a potential in reducing mechanical hypernociception/inflammatory response, cardiovascular and gastric lesions, anticonvulsant and antidiarrheal activities [51].…”
Section: Othersmentioning
confidence: 99%
“…A small amount of literature suggests that CaMK IV has tumor-suppressive effects and can inhibit cell proliferation while promoting apoptosis. CaMK IV can inhibit the proliferation of HepG2 and neuroblastoma cells (SH-SY5Y) by binding with coumarin to increase its activity [30] . Lin et al [31] suggested that CaMK IV is an important regulatory factor in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Vanillin stands out for a plethora of properties and applications. Firstly, it is a safe compound with well-established therapeutic activities, such as antitumor [8,9], antimutagenic [10], antidiabetic [11], antioxidant [12], and antimicrobial [13] properties.…”
Section: Introductionmentioning
confidence: 99%